Factors Influencing The Choice of Female Sterilization at Menteng Mitra Afia Hospital Jakarta - Mutiara Mayfridana Alifa; Putri Azzahroh; Rini Kundaryanti (International Journal of Midwifery and Health Sciences, 2025)
Maternal Mortality Rate (MMR) is defined and calculated as the number of maternal deaths divided by the number of person-years lived by women of reproductive age in a population. Family Planning is a programme to reduce the MMR, one of which is with female sterilization. This study aims to determine the factors related to the the Choice of Female Sterilization at Menteng Mitra Afia Hospital in the case group and control group. The method of this research is analytical observational research using a case control design. The sample in this study consisted of 78 long-term family planning acceptors consisting of 39 case groups and 39 control groups. The sampling technique uses purposive sampling technique. The research instrument consisted of a questionnaire regarding maternal knowledge and husband's support. This questionnaire has been tested for validity and reliability with Cronbach's alpha coefficient values ​​of 0.775 (knowledge) and 0.835 (husband's support). Data were analyzed using the chi square test to determine the effect between the case group and the control group. The research results show that there is a relationship between the variables age, parity, and knowledge (p<0.05). As for the variables of female sterilization indication and husband's support, there was no significant relationship with the choice of female sterilization contraception (Female Surgical Method) at Menteng Mitra Afia Hospital Jakarta (p>0.05). Keywords: Family Planning, Female Sterilization, Maternal Mortality Rate